GERAK LITERASI KEISLAMAN UNTUK MENUNJANG PROSES PEMAHAMAN AGAMA ANAK PILANGSARI - Ahmad Rifai Rifai; Riyan Febriana; Siti Nurjanah; Nuniek Rahmatika (IAIC (Institut Agama Islam Cirebon), 2023)
The author carried out KKM-BRPPL activities in Pilangsari Village by implementing five programs, namely education, religious, environmental, health and economic or entrepreneurship programs. The problems faced are that there are not many Islamic reading books available at DTA, TPQ and local mosques, at least Koran teachers or Al-Quran teachers, lack of awareness of teenagers about Healthy Life Skills Education (PKHS), lack of public awareness of cleanliness in the environment. surroundings, as well as the reach of marketing in the economic field which is still too narrow. Problem solving that can be done with assistance is providing knowledge, understanding and training. The activity method uses counseling or socialization. In the end, the author was able to optimize the use of human resources in order to create a harmonious, intelligent and dedicated Pilangsari Village.